Restoration effect of chemically modified microRNA-143-3p on acute myocardial infarction in animal models - Shingo Minatoguchi; Nobuhiko Sugito; Kazuki Heishima; Yuko Ito; Remi Nakashima; Hiroyuki Okura; Yukihiro Akao; Shinya Minatoguchi (Scientific Reports)
Abstract We investigated whether miR143#12, a synthesized chemically modified miR-143-3p derivative, exerts therapeutic effects on acute myocardial infarction (AMI). Sprague–Dawley rats and Japanese white rabbits underwent 30 min of coronary occlusion followed by 2 weeks of reperfusion. The rat AMI model was intravenously administered with control miRNA (9 μg/kg), 3 μg/kg or 9 μg/kg of miR143#12 1 h after reperfusion, while the rabbit AMI model was intravenously administered with control miRNA (9 μg/kg) or 9 μg/kg of miR143#12. In the rat and rabbit AMI models, 9 μg/kg of miR143#12 significantly reduced infarct sizes and significantly improved cardiac function including LVEF and LVFS at 2 weeks. The tissue miR143 levels in infarct areas significantly decreased after AMI in both models. Electron microscopic study and immunohistochemistry suggested that miR143#12 suppressed autophagic cell death caused by AMI and induced neoangiogenesis in the infarct border. In cultured rat H9c2 cells, miR143#12 significantly inhibited H2O2-induced autophagic cell death by decreasing ROS levels and increased viable cell numbers more than the control by silencing COX-1, -2, and ATG7. Replacement treatment with miR143#12 in the infarct areas, where the expression levels of miR143 were significantly decreased, has a beneficial effect on AMI by silencing COX-1 and -2.